SISTEM INFORMASI GEOGRAFIS (SIG) UNTUK PEMETAAN POTENSI DAN MANAJEMEN SUMBER DAYA DESA WISATA DI KABUPATEN TASIKMALAYA - Cepi Rahmat Hidayat; Teuku Mufizar; Ariel Ivan Al-Hakim; Alfiyah Adwa (Sekolah Tinggi Teknologi Wastukancana, 2026)
Tasikmalaya Regency, located in West Java Province, has 92 Tourism Villages, but only 5 villages have developed status and the remaining 87 are still in the pilot status. Pilot villages have potential that has not been optimally managed and minimal visits, indicating an urgent need for tools to map and manage this potential so that they can be upgraded to a sustainable tourism destination. This study aims to design and build a Geographic Information System (GIS) for Potential Mapping and Resource Management of Tourism Villages in Tasikmalaya Regency, using the Waterfall software development model. This GIS is designed to visualize geospatial data on locations, assets, and potential categories of 87 pilot villages in an integrated manner. The web-based information system was successfully developed, proven by Black Box testing showing that the application runs as expected. Furthermore, the System Usability Scale (SUS) test produced a score of 75.5 (category